ASUHAN KEPERAWATAN PADA IBU HAMIL TRIMESTER III DENGAN FOKUS INTERVENSI TERAPI RENDAM KAKI AIR HANGAT KENCUR UNTUK MENURUNKAN DERAJAT EDEMA DI RUMAH SEHAT BIDAN DELIMA - Almahera, Alvie; Ati Nurhayati, Nung; Darmayanti (Yayasan Putra Sukamanah Sejahtera, 2025)
Edema in the lower extremities is one of the most common physiological discomforts experienced by pregnant women in the third trimester. The World Health Organization reported in 2020 that there was an approximately 75% increase in the incidence of foot swelling during the second and third trimesters of pregnancy. This case study aims to implement nursing care, which includes assessment, data analysis, diagnosis determination, intervention planning, implementation, evaluation, and documentation. The focus of the intervention is a warm kencur (aromatic ginger) foot soak therapy as a natural herbal remedy to reduce the degree of edema and relieve acute pain in third-trimester pregnant women. The intervention was carried out for five consecutive days, with a duration of 10 minutes per day. Evaluation results showed a reduction in the degree of edema and pain scale. On the first day, the client experienced grade 3 edema, which decreased to grade 2 by the third day and reached grade 1 by the fifth day. This indicates that warm kencur foot soak therapy is effective in reducing the degree of edema in third-trimester pregnant women. The author recommends that third- trimester pregnant women experiencing foot edema regularly perform warm kencur foot soak therapy to help reduce swelling.